Social Support of Parents on Medication Adherence to Tuberculosis Patients in Children - Farida Wahyu Ningtyias; Iken Nafikadini; Afif Hamdalah; Wahyu Muldayani (Health Notions, 2021)
Adherence to taking this medication is needed in all diseases, especially TB disease, because this disease requires extra supervision in its treatment. Adherence to medication behavior is basically influenced by several factors, one of which is social support from those closest to the patient. Support can be obtained from the patient's family (father and mother), who always monitor the progress of patients. The 4 basic forms of social support, namely emotional support, instrumental support, informative support and reward support. This was qualitative research. Focus group discussion with 12 informants used for collected data. Results of this research showed that parents gave social supports i.g emotional support, instrumental support, informative support and reward support which related with medication adherence. Keywords: social support; parents; medication adherence; tuberculosis; children